UNIDADES DE POLÍCIA PACIFICADORA (UPPS) NO RIO DE JANEIRO: HISTÓRIA E PLANEJAMENTO ESTRATÉGICO SITUACIONAL EM AÇÃO - Franco, Andréa Marinho de Souza (2012)
This thesis aims to historicize the planning of Pacification Police Units (UPP) in Rio de Janeiro, analyzing the initiative from the perspective of characters who participated in its formulation and the first steps towards its implementation. Were identified and interviewed the main actors in the implementation process of the UPPs, used the technique of oral history. This research methodology allows you to retrieve information that is not available in documents, but the stories of people who participated in or witnessed, certain phenomena, events, situations. Based on the oral testimony of persons; his story to narrate an event or at least reminded of how a given phenomenon., Allows you to assign different settings of importance or perception of the facts from the perspective of each participant. The interview transcripts were analyzed on the situational perspective of strategic planning (SSP), allowing highlighted the main joints between the actors involved and show the dynamics of planning. The contribution of this dissertation was to demonstrate how was the planning of UPPs from the theoretical framework offered by the Situational Strategic Planning (SSP) in the four moments: the explanatory and the normative, strategic and tactical operations. The role of chief planner and executor of UPPs was exercised by the Secretary of Public Safety that intuitively tied according to the logic of the PES. Guiding its action in understanding what is possible or elect a plan, but you can not choose the circumstances in which it is taking place. Planning is then a set almost controlled. The Secretary acted in four stages proposed by Matus. First identified the situation of public security as a chess board, making an accurate diagnosis and explained clearly, without disguise the situation lived by the state, providing thus an explanation of the problem. In sequence, an action that emerges is born of an opportunity that arose from the fact that the community of "Dona Marta," dominated by traffic, have become headless. Decide if this opportunity to articulate an action plan taking advantage of that single moment. It also stands out in the strategic moment, the definition and implementation of an "other" training strategy that would guarantee the professional profile required to support the project. And finally when they are articulating the tactical and operational actions which are proper of Public Safety and those to be implemented in other parts of government, from the perception that security is not only perpetuates the UPP's as a state policy. (MATUS, 1991, p 31). Note also a "make" and "remake" continued the statement from the Secretary that each occupation is a unique experience because it considers the social actors themselves and different in each community. The research has also shown that for the same fact, the implementation of the UPP's, there are different interpretations by different actors about the chronology and actions that resulted in this deployment. This difference is explained by the PES that takes into account that different actors come to reality by angles and interests.